2018
DOI: 10.3390/molecules23112988
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated LC-MS-Based Strategy for the Quality Assessment and Discrimination of Three Panax Species

Abstract: The quality assessment and discrimination of Panax herbs are very challenging to perform due to the complexity and variability of their chemical compositions. An integrated strategy was established using UHPLC-Q-Exactive/HRMS and HPLC-ESI-MS/MS to achieve an accurate, rapid, and comprehensive qualitative and quantitative analysis of Panax japonicas (PJ), Panax japonicus var. major (PM), and Panax zingiberensis (PZ). Additionally, discrimination among the three species was explored with partial least squares–di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Untargeted metabolomics has become a mature approach in holistically exploring the differential components from different chemical groups at the metabolome level, and covers extensive applications in the authentication of TCM. The troublesome issues, such as differentiation among the easily confusing species [7,8], different geographic origins [9], different parts from the same plant [10], different ages [11,12], and different processing technologies [13], can be accomplished by untargeted metabolomics workflows. Untargeted metabolomics is typically performed following four steps: (i) acquisition of metabolic features by direct infusion or chromatography/MS hyphenation techniques; (ii) deconvolution including peak alignment and peak picking generating a peak table; (iii) multivariate statistical analysis by unsupervised or supervised classifiers to unveil the components associated with groups segregation, and (iv) quantitative assay or validation process to rationalize the discovered chemical or biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Untargeted metabolomics has become a mature approach in holistically exploring the differential components from different chemical groups at the metabolome level, and covers extensive applications in the authentication of TCM. The troublesome issues, such as differentiation among the easily confusing species [7,8], different geographic origins [9], different parts from the same plant [10], different ages [11,12], and different processing technologies [13], can be accomplished by untargeted metabolomics workflows. Untargeted metabolomics is typically performed following four steps: (i) acquisition of metabolic features by direct infusion or chromatography/MS hyphenation techniques; (ii) deconvolution including peak alignment and peak picking generating a peak table; (iii) multivariate statistical analysis by unsupervised or supervised classifiers to unveil the components associated with groups segregation, and (iv) quantitative assay or validation process to rationalize the discovered chemical or biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…P. zingiberensis is widely used in folk medicines in China and Myanmar to strengthen the immune response and provide cardiovascular protection [ 41 ]. It exhibits anticancer activity and prevents platelet aggregation because of the presence of a large number of OA-type ginsenosides, such as ginsenoside Ro, chikusetsu saponin-IV (CS-IV) and CS-Iva; PPT-type ginsenosides (Rg1, Re, and F3) are also present in P. zingiberensis at higher concentrations than the PPD-type ginsenosides [ 39 , 42 ]. Zingibroside R1 has also been detected in P. zingiberensis and has a structure similar to the OA-type ginsenoside Ro, although it lacks glucose at the C28 position [ 39 ].…”
Section: Comparison Of the Major Ginsenosides In Various mentioning
confidence: 99%
“…As illustrated in Figure 6, more than half of the bioactive constituents investigated in this study showed significant difference between xylem and phloem. Xylem contained a dramatically higher amount (p < 0.05) of catechin (4), epicatechin (6), dihydroquercetin (8), genistin (9), ononin (11), liquiritigenin (12), daidzein (13), calycosin (14), naringenin (15), genistein (16), isoliquiritigenin (18), formononetin (19), medicarpin (20) and biochanin A (22) than the phloem. However, phloem displayed remarkably higher content (p < 0.05) of protocatechuic acid (2).…”
Section: T-test Of Samplesmentioning
confidence: 99%
“…Epicatechin (6), rutin (10), kaempferol (17) and formononetin (19) were purchased from the Chinese National Institute for the Control of Pharmaceutical and Biological Products (Beijing, China). Ononin (11), gallocatechin (1), epigallocatechin (3) and isoliquiritigenin (18) were purchased from Chengdu Chroma Biotechnology Co., Ltd. (Chengdu, China). Daidzein (13) and protocatechuic acid (2) were purchased from Shanghai Yuanye Biotechnology Co., Ltd. (Shanghai, China).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation